Efecto de la temperatura en isotermas de adsorción de avena (avena sativa) en hojuelas - Crispín Ulloa, Luis Ángel (2015)
The aim of this study was to evaluate the effect of three temperatures 25 ° C, 35 ° C and 45 ° C in the adsorption isotherms oat (Avena sativa) flakes, by the experimental determination of sorption isotherms for the static gravimetric method. The method consisted of placing a sample of 1 g of oat (Avena sativa) flakes (in triplicate), which was placed on a perforated plastic container, before being placed in each of the 7 glass containers tightly closed packings for experiment, each of these vials containing specific humidity solution, in this case we used sulfuric acid (H2SO4) of known water activity from 0.005 to 0.95, and conditioned in temperature controlled cabinets (25, 35, 45 ° C) for 15 days. The experimental values of the adsorption isotherms were fitted to six mathematical models applied in foods such as GAB, BET, Halsey, Oswin, Caurie and Smith. The quality of fit was assessed with regression coefficient (R2) and the percentage of mean relative error (% E). In the end it was concluded that the best model BET was the best fit to the experimental data, with R2 of 0.9326, 0.938 and 0.997, and 5.623% E, 6,596 and 8,337, for temperatures of 25, 35 and 45 ° C respectively. The shelf life was estimated in terms of water permeability and its effect on permeability, obtaining an estimated life ranges 29-27, 23-19 y 13-9 months.